SEROLOGICAL IDENTIFICATION OF OVINE PARATUBERCULOSIS IN VERACRUZ, MEXICO - VERGARA-REYES, REBECA ISABEL; MARTINEZ-HERRERA, DAVID ITZCOATL; LUNA-RODRIGUEZ, MAURICIO; FLORES-PRIMO, ARGEL; MENDOZA-CERVANTES, GUILLERMO; SANGABRIEL-CONDE, WENDY; VILLAGOMEZ-CORTES, JOSE ALFREDO (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
This study aimed to determine the presence of Mycobacterium avium subspecies paratuberculosis (MAP) in three sheep production regions in the state of Veracruz, México. The study regions were the Totonaca, Capital, and Tuxtlas. The study included 414 animals distributed in 55 farms. Ewes and males used as rams over three months old were randomly selected to collect serum for its subsequent analysis by indirect ELISA standard kits. Overall seroprevalence was 0.96% (IC95% 0.02-1.90), 23.07% (IC95% 0.017-45.98) by municipality, and 5.45% (IC95% 0.00-11.46) by flock. This could be the first report of exposition to MAP in sheep from the state of Veracruz. Since it is the third ovine producer in Mexico, the undetected threat of paratuberculosis (PTB) could induce economic losses and commercial disadvantage to producers. Meanwhile, the subclinical animals deemed as seropositive in this study, could be use as breed. Therefore, subclinical animals might maintain and disseminate the pathogen within herds. Furthermore, exposure to MAP was identified in the three regions studied (which have different climate conditions). These results confirm the environmental resistance of MAP and imply a health risk to ruminants and other susceptible species. Besides, in extensive livestock production, local wildlife could acquire MAP and transmit to other flocks or regions. None of the studied variables were considered as risk factor associated with MAP. Results suggest the need to develop further research to establish the distribution and impact of MAP in Veracruz. This work also prompts to enhance biosecurity measures amongst ovine producers.